Efficacy of massage versus massage with post isometric relaxation in temporomandibular disorders: a randomized controlled trial - Mahnoor Tariq; Kainaat Fatima; Shahzada Faiz Ahmad Khan; Wajeeha Mahmood; Tahir Mahmood; Sarma Khurshaid; Masooma Khalid; Mehrunisa Khoosa; Muhammad Naveed Babur (BMC, 2024)
Abstract Background Temporomandibular joint disorder (TMD) is a common condition affecting the masticatory muscles and joint mobility. Objectives The primary objective was to compare the effects of massage therapy alone and massage therapy combined with post-isometric relaxation exercises in patients with TMD for pain and maximal mouth opening. Design Assessor-blinded randomized controlled trial. Setting Sir Ganga Ram Hospital, Chaudhry Muhammad Akram Dental Hospital, Lahore Medical and Dental Hospital. Subjects Temporomandibular joint disorder patients. Intervention Group A (n = 23) received conventional treatment including massage and therapeutic exercises consecutively for 2 weeks. Group B (n = 23) received post-isometric relaxation technique along with conventional treatment for consecutive 2 weeks. Main measures The main outcome measures were pain and maximal mouth opening. Pain was measured using the Visual Analogue Scale (VAS) and maximal mouth opening (MMO) was measured using the TheraBite Scale. Results Both groups demonstrated significant improvements in pain and MMO scores post-treatment. However, Group B (massage with post-isometric relaxation exercises) showed significantly better outcomes compared to Group A (massage alone). There was a statistically significant difference in post-treatment pain scores (P = 0.000) and MMO scores (P = 0.000) between the two groups. Conclusion The results suggest that massage therapy combined with post-isometric relaxation is more effective than massage therapy alone in managing pain and improving mouth opening in TMD patients. The study provides evidence supporting the use of these therapies in TMD management. Trial registry number NCT05810831. Date of registration/First submission: 15 March 2023.